Pengaruh Penambahan Limbah Cangkang Tiram Terhadap Stabilisasi Tanah Daerah Rawa - Agus Salim; Cut Rahmawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
This study aims to determine the effect of the addition of oyster shell waste as a stabilizing material to the value of the CBR (California Bearing Ratio) and peat soil direct shear. According to USCS land is greater than 50%. The addition of oyster shell waste is done with variations of 0%, 5%, 10%, and 15%. The results of the value of dry weight (mengalamik) increased in the variation of the mixture of 0% by 0.86 gr / cm3 in the original soil and 15% by 0.946 gr / cm3 in the oyster shell mixture because this was due to the soil pores filled with stabilization vectors. The CBR value increased from 1.63% in the original soil to 11.62% in the 15% mixture of oyster shell waste. filling empty pores. The value of the shear angle increased by 20,230 in the subgrade to 33,370 in the 15% oyster shell mixture due to the chemical reaction contained in the oyster shell waste. The cohesion value (c) was 0.12 kg / cm2 in the original soil and increased by 0.13 kg / cm2 in the mixing of 15% oyster shell waste. The value of shear strength increased 0.18 kg / cm2 on the original soil and increased 0.31 kg / cm2 on the addition of 15% oyster shell waste.